2022
DOI: 10.1136/bmjgh-2022-009408
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to HIV and syphilis rapid diagnostic testing in antenatal care settings in low-income and middle-income countries: a systematic review

Abstract: BackgroundTesting and treatment during pregnancy is a well-established and cost-effective prevention strategy, which relies largely on use of rapid diagnostic tests (RDTs). Yet, in many low-income and-middle-income countries, the uptake of RDTs is suboptimal. A qualitative meta-synthesis was conducted to identify the barriers and enablers to use of HIV and syphilis RDTs among pregnant women in low-income and middle-income countries.MethodsThis review was conducted using PRISMA guidelines. Eligible studies incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 98 publications
(452 reference statements)
0
12
0
Order By: Relevance
“…A systematic review noted that among 13 studies from low and middle income countries that reported on the availability of point-ofcare diagnostic testing for syphilis, malaria, HIV, hepatitis B virus, blood pressure, diabetes, and dyslipidaemia, 11 described frequent stock-outs of test kits [33]. Similar issue regarding the clinical supply stock-outs was also noted in a recent systematic review on barriers of HIV and syphilis rapid diagnostic tests in antenatal care settings in low and middle income countries [34]. This points to the importance of strong supply chain management when planning for the scale-up of EMTCT programmes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A systematic review noted that among 13 studies from low and middle income countries that reported on the availability of point-ofcare diagnostic testing for syphilis, malaria, HIV, hepatitis B virus, blood pressure, diabetes, and dyslipidaemia, 11 described frequent stock-outs of test kits [33]. Similar issue regarding the clinical supply stock-outs was also noted in a recent systematic review on barriers of HIV and syphilis rapid diagnostic tests in antenatal care settings in low and middle income countries [34]. This points to the importance of strong supply chain management when planning for the scale-up of EMTCT programmes.…”
Section: Discussionmentioning
confidence: 75%
“…The research only took the views of health providers and policymakers. The intention was to explore the views and experiences of those implementing the EMTCT program in Indonesia, complementing earlier studies exploring the experiences of pregnant women in Indonesia on HIV and syphilis testing [ 21 ] and in other low and middle income countries [ 34 ]. Future interdisciplinary studies on challenges in implementing EMTCT program would benefit from jointly exploring the views of pregnant women, their partners, health cadres, and community organizations in the same study setting.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study corroborated the need for ongoing training. 10 , 11 , 13 , 24 , 25 Procedures initially found to be difficult can be accomplished with more training and practice. 10 , 23 Training should include start-to-finish instructions, minimise abstract concepts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Refugees' mistrust and opposition to the healthcare system resulted from this condition (Abrahamsen, 2019;Id et al, 2022;. This was also shown by articles that were published all over the world and said that healthcare services for refugees were inadequate because of a variety of obstacles (Davidson et al, 2022;Korri et al, 2021;Zhang et al, 2022). The healthcare system particularly marginalises immigrants (Albright et al, 2022).…”
Section: Discussionmentioning
confidence: 99%